Barriers to and enablers of healthy lifestyle behaviours in adolescents with obesity: a scoping review and stakeholder consultation. (18th September 2017) - Kebbe, M.; Damanhoury, S.; Browne, N.; Dyson, M. P.; McHugh, T.‐L. F.; Ball, G. D. C.
Summary: Healthy lifestyle behaviours are key to successful weight management, but have proven to be challenging to attain for adolescents with obesity. The purpose of our scoping review was to (i) describe barriers and enablers that adolescents with obesity encounter for healthy nutrition, physical activity, sedentary behaviour and sleep habits and (ii) identify gaps in the literature. We adhered to established methodology for scoping reviews. Six databases were searched (1980–June 2016) for original articles published in English or French that focused on lifestyle behaviours of 13‐ to 17‐year‐olds in paediatric weight management. Following screening and data extraction, findings of selected articles were synthesized thematically using a social ecological framework. Stakeholder consultation ( n = 20) with adolescents with obesity and health professionals was completed to enhance methodological rigour. Our search yielded 17 articles for inclusion, including 546 unique participants. Barriers to healthy nutrition and physical activity were more consistently related to individual‐level and interpersonal‐level factors; enablers tended to be linked with interpersonal‐level factors. Knowledge gaps identified related to sedentary behaviour and sleep as well as environmental and policy levels of influence. Our review revealed that some barriers and enablers were unique to adolescents with obesity, which were either within or beyond their control. These findings highlight the importance of multilevel interventions to enable healthy lifestyle behaviours for weight management.